(untitled) (Development Service Industry Management, 2025)
The purpose of the article is to substantiate the need to study a wide range of variable factors for making management decisions by small and medium-sized businesses and international companies in Ukraine under conditions of uncertainty. The relevance of the topic is due to the fact that modern Ukrainian business operates under a high level of uncertainty caused by political, economic and security challenges. In such conditions, enterprises are forced to constantly adjust and adapt business strategies, which is impossible without taking into account changes in the external and internal environment and industry characteristics. The study applies a systematic approach, methods of generalization, deduction, induction, and abstract and logical analysis. The nature and types of external, internal and market factors and the peculiarities of companies’ response to them are determined. The results of an expert survey of business owners in the market of gardening equipment, which was conducted to obtain feedback, are analyzed. It is found that over the past two years, the «portrait» of the target audience and consumer preferences have changed, and entrepreneurs focus on maintaining market status and strengthening cooperation with the leader by expanding the service. Based on the data, the author suggests directions for adapting the business strategies of companies in the market of gardening equipment. The results of the study are of practical importance for domestic enterprises and will become a starting point for further research on the decision-making process.